Construct a customer database from PDF bank statements using Python programming and Microsoft SQL - Nandi, Bikash Kumar (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.